The Effects of the PBL Based on the Socioscientific Issue Approach on Interdisciplinary Thinking and Argumentation Skills - Firnindia Putri; Sri Rahayu Lestari; Hadi Suwono (BIOEDUKASI, 2023)
The independent curriculum directs the education sector to develop socioscientific issues (SSI)-related interdisciplinary reasoning and argumentation skills that can be applied to biology education. This study aims to investigate the effects of the PBL-SSI model on students' interdisciplinary thinking and argumentation skills. This study used a Quasi Experimental design non-equivalent control group pretest-posttest design. The participants in this investigation were 71 10th grade students. Students were separated into two groups and evaluated using distinct learning models: (1) PBL-SSI, 11 males and 24 females; (2) PBL, 12 males and 24 females. PBL-SSI enhances the students' argumentation and interdisciplinary thinking skills in compared to PBL. PBL-SSI had an effect on inter-disciplinary reasoning and argumentation skills (p<0.05), according to the investigation results. PBL-SSI improved interdisciplinary thinking and argumentation skills more effectively than PBL.